Trần Anh Tuấn

\(\sqrt{5}\)x -y =\(\sqrt{5}\left(\sqrt{3}-1\right)\)

{\(2\sqrt{3}\)x +\(3\sqrt{5}\)y = 21

Giải hệ phương trình trên bằng phương pháp thế

 

Toru
Hôm kia lúc 21:04

\(\begin{cases} \sqrt5 x-y=\sqrt5(\sqrt3-1)\\ 2\sqrt3x+3\sqrt5y=21 \end{cases} \\\Leftrightarrow \begin{cases} y=\sqrt5x-\sqrt{3}.\sqrt5+\sqrt5\\ 2\sqrt3x+3\sqrt5(\sqrt5x-\sqrt3.\sqrt5+\sqrt5)=21\end{cases} \\\Leftrightarrow \begin{cases} y=\sqrt5(x-\sqrt3+1)\\ (15+2\sqrt3)x=15\sqrt3+6 \end{cases} \\\Leftrightarrow \begin{cases} y=\sqrt5(\sqrt3-\sqrt3+1)=\sqrt5\\ x=\sqrt3 \end{cases} \)

Vậy: ...

Bình luận (0)
HT.Phong (9A5)
Hôm kia lúc 21:07

\(\left\{{}\begin{matrix}\sqrt{5}x-y=\sqrt{5}\left(\sqrt{3}-1\right)\\2\sqrt{3}x+3\sqrt{5}y=21\end{matrix}\right.\)

\(\Leftrightarrow\left\{{}\begin{matrix}y=\sqrt{5}x-\sqrt{5}\left(\sqrt{3}-1\right)=\sqrt{5}x-\sqrt{15}+\sqrt{5}\\2\sqrt{3}x+3\sqrt{5}\left(\sqrt{5}x-\sqrt{15}+\sqrt{5}\right)=21\end{matrix}\right.\)

\(\Leftrightarrow\left\{{}\begin{matrix}y=\sqrt{5}x-\sqrt{15}+\sqrt{5}\\2\sqrt{3}x+15x-15\sqrt{3}+15=21\end{matrix}\right.\)

\(\Leftrightarrow\left\{{}\begin{matrix}y=\sqrt{5}x-\sqrt{15}+\sqrt{5}\\2\sqrt{3}x+15x=6+15\sqrt{3}\end{matrix}\right.\)

\(\Leftrightarrow\left\{{}\begin{matrix}y=\sqrt{5}x-\sqrt{15}+\sqrt{5}\\x=\dfrac{6+15\sqrt{3}}{2\sqrt{3}+15}\end{matrix}\right.\)

\(\Leftrightarrow\left\{{}\begin{matrix}y=\sqrt{5}\cdot\sqrt{3}-\sqrt{15}+\sqrt{5}\\x=\sqrt{3}\end{matrix}\right.\)

\(\Leftrightarrow\left\{{}\begin{matrix}y=\sqrt{5}\\x=\sqrt{3}\end{matrix}\right.\)

Vậy: ...

 

Bình luận (0)

Các câu hỏi tương tự
Khánh An Ngô
Xem chi tiết
Bùi Anh Tuấn
Xem chi tiết
Hoàng Phúc
Xem chi tiết
Nguyễn Như Mai
Xem chi tiết
fan FA
Xem chi tiết
Kiều Phương Phạm
Xem chi tiết
Phùng Minh Phúc
Xem chi tiết
Nott mee
Xem chi tiết
nguyen la nguyen
Xem chi tiết
Rhider
Xem chi tiết